Visual Gene Expression Reveals a cone-to-rod Developmental Progression in Deep-Sea Fishes. (25th September 2021) - Lupše, Nik; Cortesi, Fabio; Freese, Marko; Marohn, Lasse; Pohlmann, Jan-Dag; Wysujack, Klaus; Hanel, Reinhold; Musilova, Zuzana
Abstract: Vertebrates use cone cells in the retina for color vision and rod cells to see in dim light. Many deep-sea fishes have adapted to their environment to have only rod cells in the retina, while both rod and cone genes are still preserved in their genomes. As deep-sea fish larvae start their lives in the shallow, and only later submerge to the depth, they have to cope with diverse environmental conditions during ontogeny. Using a comparative transcriptomic approach in 20 deep-sea fish species from eight teleost orders, we report on a developmental cone-to-rod switch. While adults mostly rely on rod opsin ( RH1 ) for vision in dim light, larvae almost exclusively express middle-wavelength-sensitive ("green") cone opsins ( RH2 ) in their retinas. The phototransduction cascade genes follow a similar ontogenetic pattern of cone—followed by rod-specific gene expression in most species, except for the pearleye and sabretooth (Aulopiformes), in which the cone cascade remains dominant throughout development, casting doubts on the photoreceptor cell identity. By inspecting the whole genomes of five deep-sea species (four of them sequenced within this study: Idiacanthus fasciola, Chauliodus sloani ; Stomiiformes; Coccorella atlantica, and Scopelarchus michaelsarsi ; Aulopiformes), we found that they possess one or two copies of the rod RH1 opsin gene, and up to seven copies of the cone RH2 opsin genes in their genomes, while other cone opsin classes have been mostly lost. Our findings hence provide molecular evidence for a limited opsin gene repertoire in deep-sea fishes and a conserved vertebrate pattern whereby cone photoreceptors develop first and rod photoreceptors are added only at later developmental stages.